Viral Escape Mutant Epitope Maintains TCR Affinity for Antigen yet Curtails CD8 T Cell Responses - Shorter, Shayla K. (PLoS One, 2016)
T cells have the remarkable ability to recognize antigen with great specificity and in turn mount an appropriate and robust immune response. Critical to this process is the initial T cell antigen recognition and subsequent signal transduction events. This antigen recognition can be modulated at the site of TCR interaction with peptide:major histocompatibility (pMHC) or peptide interaction with the MHC molecule. Both events could have a range of effects on T cell fate. Though responses to antigens that bind sub-optimally to TCR, known as altered peptide ligands (APL), have been studied extensively, the impact of disrupting antigen binding to MHC has been highlighted to a lesser extent and is usually considered to result in complete loss of epitope recognition. Here we present a model of viral evasion from CD8 T cell immuno-surveillance by a lymphocytic choriomeningitis virus (LCMV) escape mutant with an epitope for which TCR affinity for pMHC remains high but where the antigenic peptide binds sub optimally to MHC. Despite high TCR affinity for variant epitope, levels of interferon regulatory factor-4 (IRF4) are not sustained in response to the variant indicating differences in perceived TCR signal strength. The CD8+ T cell response to the variant epitope is characterized by early proliferation and up-regulation of activation markers. Interestingly, this response is not maintained and is characterized by a lack in IL-2 and IFNγ production, increased apoptosis and an abrogated glycolytic response. We show that disrupting the stability of peptide in MHC can effectively disrupt TCR signal strength despite unchanged affinity for TCR and can significantly impact the CD8+ T cell response to a viral escape mutant.